The Philosophy of Evil from the Perspective of Imam Ali - reza mahdavi azarboni; maryam alizadeh (پژوهش نامه معارف قرآنی, 2011)
The problem of evil and the mystery of its existence were and are still a continuous issue in philosophical discussions. All religions of the world and philosophical schools of thought have been involved with this problem and many different responses have emerged and proposed depending on their world view. Muslim philosophers have paid a significant and more serious attention to the issue. ln addition, in the light of Quran and Sunnah various explanations and reasonable interpretations have been given. This study is aimed at dealing with the problem of evil. Furthermore, It attempts to give a rational understanding and solution to the problem of evil on the basis of Imam Ali's teachings and narrations.